Application of phase change material to save air conditioning energy in building. - Indartono, Yuli S.; Suwono, Aryadi; Pasek,Ari D.; Christantho, Alexander
Energy saving in Air Conditioning (AC) system is quite important for climate-change mitigation, sinceACsystem consumes around 60% ofbuilding electricity.Air conditioning technologyalso deals withozone depletionproblem. Chilled-water AC system needs smaller amount of primary refrigerant, so itcan minimizepossible CFC or HCFC(Ozone Depleting Substances)emission into the atmosphere.Latent heat transportation system applied in chilled-water system open opportunity to save energy. In the second aspect, integration of Phase Change Material (PCM) in building wall can increase heat capacity of the wall and reduce and stabilize indoortemperature. Both technologies can mutually contribute in reducing AC energy consumption. In this paper, application of some PCMs in chilled water system and wall model are reported.
Keywords: Concrete block; Air conditioning; Energy saving; Phase change material